Study of the effects of spray‐drying on the functionality of probiotic lactobacilli - Paez, Roxana Beatriz; Lavari, Luisina; Audero, Gabriela Maria; Cuatrin, Alejandra; Zaritzky, Noemi Elisabet; Reinheimer, Jorge Alberto; Vinderola, Celso Gabriel (2018)
Three probiotic lactobacilli strains were spray‐dried in 20% (w/v) skim milk and submitted to a simulated gastrointestinal digestion. Fresh or spray‐dried cultures were administered to mice for 5 and 10 days, and Immunoglobulin A (IgA)‐producing cells were enumerated in the small intestine by immunohistochemistry. Spray‐drying significantly enhanced the resistance of Lactobacillus paracasei A13 and Lactobacillus casei Nad to a simulated gastrointestinal digestion (0.96 and 1.95 log orders, respectively), compared with fresh cultures. Also, a significant higher number of IgA‐producing cells were induced by spray‐dried cultures compared with fresh cultures. Spray‐drying is a suitable, but strain‐dependent, technological process for the development of probiotic cultures in skim milk with increased functionality.